TRACE STYLISTICS OF PARALLEL CONSTRUCTION IN BARRACK OBAMA’ SPEECH ENTITLED ‘A MORE PER UNION’ - Islam, Aang Fatihul (JEELL (Journal of English Education, Linguistics and Literature), 2014)
This article concerned with Stylistics of Pararel Construction of speech ‘A More Per Union’ by Barrack Obama. This study investigated how Barrack Obama applied Pararel Construction in his speech entitled ‘A More Per Union’ in order to persuade the listener through his speech. It was indicate that stylistics gave contribution to persuade the reader used the beauty of language.The article uses stylistics approach, qualitative descriptive, where the approach is limited on research of Linguistics research. It had taken the data to analyze, which was the speech of  ‘A More Per Union’ from audio which transcription into script . The instrument used here was human instrument because the researcher acted as the organizer of the research and also the only instrument to collect the data.The result of finding show that: (1) Barrack Obama in ‘A More Per Union’ speech used some kinds of Pararel Construction namely: Adjective/Adjective phrase parallelism, Noun/Noun phrase parallelism, Adverb/Adverbial phrase parallelism, Clause parallelism, infinitive parallelism, -ing form parallelism, and Verb/Verb phrase parallelism, (2) Out of 178 sentences in Obama's speech entitled ‘A More Perfect Union’, 112 sentences (62,9%) contain parallel structure, In ‘A More Per Union’ speech, Barrack Obama in fact applied some of stylistics Pararel Construction: adjective 11,7 %, adverb 8,5 %, clause 38,25 %, infinitive 7,5 %, ing 5,3 %, noun 68, 45 %, and verb 15,10 (3) the function of some kinds of Pararel Construction used by Barrack Obama are cordination, emphasize, and sequence. Keywords: : Stylistics, Pararel Construction, Speech, A More Per Union